2021
DOI: 10.1371/journal.pone.0244550
|View full text |Cite
|
Sign up to set email alerts
|

“As young men we have a role to play in preventing sexual violence”: Development and relevance of the men with conscience intervention to prevent sexual violence

Abstract: Sexual violence against women and girls is a major public health problem globally and in South Africa. Although young men have been identified as an important risk group for prevention interventions, scant attention have been given to this age cohort in low and middle-income countries. There is strong evidence that perpetration starts early and increasing attention is being drawn to Higher Education Institutions (HEIs) as settings for prevention interventions. The main objective of this study was to adapt the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Finally, the last type of intervention utilized was school-based programs to prevent dating violence ( N = 3). School-based programs included group learning sessions for adolescents in secondary school to learn how to develop healthy interpersonal relationships (Baiocchi et al, 2017; Decker et al, 2018; Edwards et al, 2022) and group sessions in universities to help young adult men unlearn unhealthy attitudes toward violence, masculinity, and relationships (de Villers et al, 2021). For example, IMPower is a 6-week program designed to provide life skills training to primary and secondary school girls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the last type of intervention utilized was school-based programs to prevent dating violence ( N = 3). School-based programs included group learning sessions for adolescents in secondary school to learn how to develop healthy interpersonal relationships (Baiocchi et al, 2017; Decker et al, 2018; Edwards et al, 2022) and group sessions in universities to help young adult men unlearn unhealthy attitudes toward violence, masculinity, and relationships (de Villers et al, 2021). For example, IMPower is a 6-week program designed to provide life skills training to primary and secondary school girls.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have found that girls are forced to marry at a young age in exchange for food or livestock when droughts or floods destroy crops (Cwienk, 2020;Pope et al, 2022;UNFPA, 2021b). Transactional sex exchange (jaboya) is a recognized issue in coastal Kenyan regions where women are forced to engage in sex to gain access to fish; declining fish populations have exacerbated this issue (Davis & Silver, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Program designers may also wish to consider evaluation at both participant and institutional level. Care should be taken to ensure that the course's status as elective or required is considered for evaluation purposes (Darby, 2006). Significant research is required to bring gender mainstreaming to higher education.…”
Section: Delivery Implementation and Evaluationmentioning
confidence: 99%